MiR-27a-3p binds to TET1 mediated DNA demethylation of ADCY6 regulates breast cancer progression via epithelial-mesenchymal transition - Wu, Hao; Qiu, Juanjuan; Wu, Zhenru; He, Tao; Zhou, Chen; Lv, Qing (Frontiers in Oncology, 2022)
Introduction: Adenylyl cyclase isoform 6 (ADCY6) is a member of membrane-bound adenylate cyclase family that converts adenosine triphosphate (ATP) into cAMP and pyrophosphate. An increasing number of researchers have studied the role of ADCY6 in cancer. However, its specific role in breast cancer remains unknown. Methods: Bioinformatics and clinical data were used to analyse the expression of ADCY6 in breast cancer. ADCY6 DNA methylation was analysed using DNA methylation-specific PCR and Bisulfite Sanger sequencing. Using lentiviral stable miRNA transfection together with cell biology functional assays and gene expression/ target analysis, we investigated the interaction between miR-27a-3p, TET1 and ADCY6 in breast cancer. Results: We found that ADCY6 is expressed at low levels in breast cancer and leads to increases in the proliferation, invasion and migration of breast cancer cells. The low expression of ADCY6 is due to the lower demethylation of ten-eleven translocation methylcytosine dioxygenase 1 (TET1), and the methylation of ADCY6 can be altered by TET1. More importantly, bioinformatics analysis showed that TET1 is regulated by miR-27a-3p and regulates the methylation of ADCY6 to affect the EMT process of breast cancer cells, thereby affecting the malignant biological behaviour of breast cancer. Conclusions: Our study demonstrates that the methylation modification of ADCY6 is regulated by TET1 and leads to ADCY6 activation. miR-27a-3p negatively regulates the expression of TET1 and affects the EMT process of breast cancer through ADCY6, thereby promoting the malignant biological behaviour of breast cancer. Our results may provide new research ideas and directions for DNA methylation and EMT changes in breast cancer.